2019
DOI: 10.3390/nu11081749
|View full text |Cite
|
Sign up to set email alerts
|

Filbertone Ameliorates Adiposity in Mice Fed a High-Fat Diet via Activation of cAMP Signaling

Abstract: The aim of this research was to estimate the preventive effects of filbertone, the main flavor compound in hazelnuts, on lipid accumulation in the adipose tissue of mice fed a high-fat diet (HFD) and to reveal the underlying molecular mechanisms. Male C57BL/6N mice were fed chow, a HFD, or a 0.025% filbertone-supplemented HFD for 14 weeks. We found that filbertone supplementation resulted in significant reductions in body weight gain and lipid accumulation in adipose tissue, with parallel improvements in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…[56] The cAMP signaling pathway is thus pivotal in regulation of adipose tissue development and function, and it has become a therapeutic target of certain antiobesity phytochemicals. For example, Moon et al [4] reported that filbertone, a major flavor compound in the fruits of hazel trees, reduced lipid accumulation in HFD-fed mice and 3T3-L1 cells by activating the cAMP pathway. Taken together, the transcriptome analysis suggested that EU significantly changed metabolism and signal pathways in epididymal WAT under high-fat feeding conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[56] The cAMP signaling pathway is thus pivotal in regulation of adipose tissue development and function, and it has become a therapeutic target of certain antiobesity phytochemicals. For example, Moon et al [4] reported that filbertone, a major flavor compound in the fruits of hazel trees, reduced lipid accumulation in HFD-fed mice and 3T3-L1 cells by activating the cAMP pathway. Taken together, the transcriptome analysis suggested that EU significantly changed metabolism and signal pathways in epididymal WAT under high-fat feeding conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high-fat diet (HFD) overconsumption is one of the leading causes of obesity. [3,4] In addition, the obesity pandemic is associated with the increasing prevalence of various other chronic diseases and infectious disease, such as type 2 diabetes mellitus, cardiovascular diseases, hypertension, and corona virus disease 2019, and therefore confers serious global public health issues. [5,6] The worldwide prevalence of obesity nearly tripled between 1975 and 2016 in accordance with the World Health Organization, and in 2016, overweight and obese people account for around 39% and 13% of the world's adult population, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…C/EBP-α is a central transcriptional adipogenic activator regulated by cAMP-responsive element-binding protein (CREB). cAMP binds to the regulatory subunit PKA and release the catalytic subunit; it phosphorylates the lipid metabolism-associated protein substrates, including AMPK, in peripheral and subcutaneous adipocytes ( Moon et al, 2019 ). AMPK activated during depletion of the cellular ATP increases the AMP/ATP ratio and initiates metabolic and genetic events to restore ATP levels via fatty acid beta-oxidation in adipocytes ( Cheng et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Piperonal, an aromatic compound found in vanilla and filbertone, the main flavor compound in hazelnuts, increases the level of cAMP in adipose tissue, decreases the body weight and plasma lipid profiles, and improves glucose tolerance in HFD-induced obese mice [ 105 , 106 , 107 ]. Obesity is well-known to contribute to the progression and development of diabetes.…”
Section: Adipose Tissuementioning
confidence: 99%